Half a century Monuments and Historic Buildings Act: 1961-2011 - Vincent van Rossem (Bulletin KNOB, 2012)
The Dutch Monuments and Historic Buildings Act dates from 1961. Naturally, the Act was primarily intended to protect old buildings. In the first place the traditional heritage: churches, town gates, town halls and the houses of aristocrats. Soon architecture from a more recent past, the period 1850-1940, was also placed on the historic buildings register. The Act as an administrative instrument for the conservation of historic buildings was a great success. Consequently, the intentions of the legislator were fully complied with, but the Act had social side effects which may have been even more important, for the Monuments and Historic Buildings Act caused a national change of mentality.